Discerning Microbially Mediated Processes During Redox Transitions in Flooded Soils Using Carbon and Energy Balances - Boye, Kristin; Herrmann, Anke M.; Schaefer, Michael V.; Tfaily, Malak M.; Fendorf, Scott (Frontiers in Environmental Science, 2018)
Recurring dry-wet cycles of soils, such as in rice paddies and on floodplains, have a dramatic impact on biogeochemical processes. The rates and trajectories of microbial metabolic functions during transition periods from drained to flooded conditions affect the transformation rates and phase partitioning of carbon, nutrients, and contaminants. However, the regulating mechanisms responsible for diverging functional metabolisms during such transitions are poorly resolved. The chemistry of organic carbon within the microbially available pool likely holds key information regarding carbon cycling and redox transformation rates. In this study, we used mesocosms to examine the influence of different carbon sources (glucose, straw, manure, char) on microbial energetics, respiration rates, and carbon balances in rice paddy soils during the transition from drained to flooded conditions following inundation. We found that variability in carbon solubility (1.6-400 mg g-1) and chemical composition of the amendments led to non-uniform stimulation of carbon dioxide production per unit carbon added (0.4-32.9 mmol CO2 mol-1 added C). However, there was a clear linear correlation between energy release and net CO2 production rate (R2=0.85), between CO2 and initial soluble C (R2=0.91, excluding glucose treatment) and between heat output and Gibbs free energy of initial soluble C (R2=0.78 and 0.69, with/without glucose respectively). Our results further indicated that the chemical composition of the soluble C from amendments initiated divergent anaerobic respiration behavior, impacting methane production and the partitioning of elements between soil solid phase and solution. This study shows the benefit of monitoring energy and element mass balances for elucidating the contribution of various microbial metabolic functions in complex systems. Further, our results highlight the importance of organic carbon composition within the water soluble pool as a key driver of microbially mediated redox transformations with major impacts on greenhouse gas emissions, contaminant fate, and nutrient cycling in paddy soils and similar ecosystems.